Identification of additional risk loci for stroke and small vessel disease: a meta-analysis of genome-wide association studies. Issue 7 (June 2016) - ,; Chauhan, Ganesh; Arnold, Corey R; Chu, Audrey Y; Fornage, Myriam; Reyahi, Azadeh; Bis, Joshua C; Havulinna, Aki S; Sargurupremraj, Muralidharan; Smith, Albert Vernon; Adams, Hieab H H; Choi, Seung Hoan; et al.
Summary: Background: Genetic determinants of stroke, the leading neurological cause of death and disability, are poorly understood and have seldom been explored in the general population. Our aim was to identify additional loci for stroke by doing a meta-analysis of genome-wide association studies. Methods: For the discovery sample, we did a genome-wide analysis of common genetic variants associated with incident stroke risk in 18 population-based cohorts comprising 84 961 participants, of whom 4348 had stroke. Stroke diagnosis was ascertained and validated by the study investigators. Mean age at stroke ranged from 45·8 years to 76·4 years, and data collection in the studies took place between 1948 and 2013. We did validation analyses for variants yielding a significant association (at p<5 × 10 −6 ) with all-stroke, ischaemic stroke, cardioembolic ischaemic stroke, or non-cardioembolic ischaemic stroke in the largest available cross-sectional studies (70 804 participants, of whom 19 816 had stroke). Summary-level results of discovery and follow-up stages were combined using inverse-variance weighted fixed-effects meta-analysis, and in-silico lookups were done in stroke subtypes. For genome-wide significant findings (at p<5 × 10 −8 ), we explored associations with additional cerebrovascular phenotypes and did functional experiments using conditional (inducible) deletion of the probable causal gene in mice. We also studied the expression of orthologs of this probable causal gene and its effects on cerebral vasculature in zebrafish mutants. Findings: We replicated seven of eight known loci associated with risk for ischaemic stroke, and identified a novel locus at chromosome 6p25 (rs12204590, near FOXF2 ) associated with risk of all-stroke (odds ratio [OR] 1·08, 95% CI 1·05–1·12, p=1·48 × 10 −8 ; minor allele frequency 21%). The rs12204590 stroke risk allele was also associated with increased MRI-defined burden of white matter hyperintensity—a marker of cerebral small vessel disease—in stroke-free adults (n=21 079; p=0·0025). Consistently, young patients (aged 2–32 years) with segmental deletions of FOXF2 showed an extensive burden of white matter hyperintensity. Deletion of Foxf2 in adult mice resulted in cerebral infarction, reactive gliosis, and microhaemorrhage. The orthologs of FOXF2 in zebrafish (foxf2b and foxf2a ) are expressed in brain pericytes and mutant foxf2b −/− cerebral vessels show decreased smooth muscle cell and pericyte coverage. Interpretation: We identified common variants near FOXF2 that are associated with increased stroke susceptibility. Epidemiological and experimental data suggest that FOXF2 mediates this association, potentially via differentiation defects of cerebral vascular mural cells. Further expression studies in appropriate human tissues, and further functional experiments with long follow-up periods are needed to fully understand the underlying mechanisms. Funding: NIH, NINDS, NHMRC, CIHR, European national research institutions, Fondation Leducq.